Development and utilization of new O 2 -independent bioreporters - Agranier, Eva; Crétin, Pauline; Joublin-Delavat, Aurélie; Veillard, Léa; Touahri, Katia; Delavat, François (Microbiology spectrum, 2024)
Fluorescent proteins are used for decades, and have allowed major discoveries in biology in a wide variety of fields, and are used in environmental as well as clinical contexts. Green fluorescent protein (GFP) and all its derivatives share a common feature: they rely on the presence of dioxygen (O 2 ) for protein maturation and fluorescence. This dependency precludes their use in anoxic environments. Here, we constructed a series of genetic circuits allowing production of KOFP-7, an O 2 -independant flavin-binding fluorescent protein. We demonstrated that Escherichia coli cells producing KOFP-7 are fluorescent, both at the population and single-cell levels. Importantly, we showed that, unlike cells producing GFP, cells producing KOFP-7 are fluorescent in anoxia. Finally, we demonstrated that Vibrio diazotrophicus NS1, a facultative anaerobe, is fluorescent in the absence of O 2 when KOFP-7 is produced. Altogether, the development of new genetic circuits allowing O 2 -independent fluorescence will open new perspective to study anaerobic processes.